Evaluation of the clinical utility of optical coherence tomography angiography in age-related macular degeneration. Issue 7 (21st August 2020) - Cavichini, Melina; Dans, Kunny C; Jhingan, Mahima; Amador-Patarroyo, Manuel J; Borooah, Shyamanga; Bartsch, Dirk-Uwe; Nudleman, Eric; Freeman, William R
Abstract : Background/Aims: To evaluate the ability of optical coherence tomography angiography (OCTA) to identify the presence or absence of choroidal neovascularisation (CNV) and CNV activity in age-related macular degeneration (AMD). Methods: Clinical parameters, fundus fluorescein angiogram and spectral-domain optical coherence tomography (SD-OCT) were used as the gold standard to determine disease activity. OCTA imaging was performed on the same day and was graded by two masked retina specialists for the presence or absence of CNV. Traditional multimodal imaging and OCTA findings were compared. Results: One hundred and fifty-two eyes of 106 patients with AMD were retrospectively reviewed. Of these, 59 eyes had wet AMD and 93 had dry AMD with high-risk drusen. OCTA had 85.4% and 79.3% specificity and sensitivity, respectively, in determining the presence or absence of CNV. OCTA was 69.5% accurate in determining active CNV. False positives and negatives were 21.6% and 8.0%, respectively. Conclusions: This study suggests that en-face OCTA images allow a moderate ability to identify CNV and that OCTA alone is weak at recognising active CNV requiring treatment in AMD.